FRI0004 Modulating FC-linked glycosylation patterns of human IGG1. (23rd January 2014) - Wang, J.; Balog, C.I.; Stavenhagen, K.; Koeleman, C.A.; Selman, M.H.; Deelder, A.M.; Huizinga, T.W.; Toes, R.E.; Wuhrer, M.; Scherer, H.U.
Abstract : Background: Glycosylation of the Fc tail of human IgG strongly influences Fc-mediated effector functions. Recently, we have shown that anti-citrullinated protein antibodies (ACPA) isolated from serum and synovial fluid of patients with rheumatoid arthritis (RA) exhibit a specific, pro-inflammatory Fc-linked glycosylation profile. This glycan pattern is distinct from the glycan residues attached to the Fc tail of non-specific total IgG. As these data indicate a potential role of Fc-linked glycans for the biological effects that ACPA exert within the pathogenesis of RA, it is of interest to understand the mechanisms that regulate the Fc-glycosylation machinery of B cells. Objectives: To study the effect of various mediators (cytokines, vitamins, microbial products) with relevance to adaptive and innate immune responses on Fc-linked glycan residues of human IgG. Methods: Peripheral blood mononuclear cells were obtained from healthy human donors. CD19 expressing B cells were isolated by magnetic bead-based positive selection and cultured in the presence of anti-IgM, IL-2 and IL-10 on a layer of irradiated, CD40L transfected fibroblasts to induce IgG production. In addition, mediators described to have immunomodulatory activity on B cells (IL-4/6/17/21, IFN-γ, TNF-α, LT-α, TGF-β, CpG, all-trans retinoic acid (ATRA)) were added to the cultures. After 7-9 days of culture, IgG molecules (IgG1, 2 and 4) were isolated from culture supernatants by protein A affinity chromatography and subjected to tryptic digest. IgG1-linked Fc-glycopeptides were analyzed by mass-spectrometry. Results: Whereas IL-21 and CpG significantly and consistently increased the degree of galactosylation and sialylation of the Fc-linked glycan, ATRA strongly decreased the frequency of these glycoforms. No significant effects were observed for the other mediators tested. Of interest, IL-21 additionally decreased the frequency of bisecting N-acteylglucosamine (GlcNAc), whereas ATRA left this sugar moiety unchanged. Once induced, the Fc-linked glycan profiles of secreted IgG1 remained stable, even after the added mediators were withdrawn after 5 days of culture. Conclusions: Our data indicate that several factors, present in the microenvironment of B cells during activation and differentiation, are capable of differentially regulating the Fc-glycosylation of IgG1. Once B cells differentiate into antibody secreting cells, the IgG1 Fc-linked glycan profile remained stable. These data further our understanding of the mechanisms underlying IgG1 Fc-glycosylation in the human and may open up novel approaches for therapeutic intervention. Disclosure of Interest: None Declared